Sexual Violence and Its Prevention in Nightlife Venues Through the Lenses of the United Nations Sustainable Development Goals – A Case Study in Ljubljana: Tinkara Bulovec, Katja Eman - Meško, Gorazd; Kutnjak Ivković, Sanja; Hacin, Rok (The UN Sustainable Development Goals and Provision of Security, Responses to Crime and Security Threats, and Fair Criminal Justice Systems, 2024)
Sexual violence prevention in nightlife venues aligns with the Sustainable Development Goals of the United Nations, promoting patron well-being, reducing inequalities, fostering gender equality, and contributing to peace, justice, and strong institutions through collaborative partnerships. The research on the perception and prevention of sexual violence in nightlife carried out in Ljubljana in 2022 involved stakeholders, nightlife personnel, and patrons. Stakeholders perceive inappropriate comments related to sexuality as the most prevalent form of nightlife sexual violence. In contrast, nightlife personnel identify unwanted physical contact as the most common form and nightlife patrons highlight unwanted advances as a prevalent form. The most commonly observed preventive measures in nightlife venues by stakeholders and patrons were security guards. Stakeholders also emphasised awareness-raising and work with youth, while personnel noted the caution and self-protective behaviour of patrons. Considering urban-specific factors is also crucial when shaping sexual violence prevention strategies.